Acquired uterine arteriovenous malformation after cesarean section - Usman, Fatimah; Sutrisno, Muhammad Al Farisi; Effendi, Kemas Yusuf; Abadi, Adnan; Manan, Heriyadi; Amran, Rizani; Zulqarnain, Iskandar (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS 1. Acquired uterine arteriovenous malformation (AVM) is an uncommon sequela of cesarean section, warranting consideration in instances of persistent uterine bleeding in the puerperium.2. Embolization represents a viable and well-established treatment modality for AVM, providing a safe and efficacious intervention that serves as an alternative, less invasive modality for patients desiring fertility preservation.   ABSTRACT Objectives: To demonstrate that embolization is a viable and well-established treatment for acquired arteriovenous malformations (AVMs), offering a safe and effective, less invasive option for patients seeking to preserve fertility.Case Report: A 20-year-old female experiencing recurrent massive bleeding with a history of previous caesarean section and wound infection resuturing. The transvaginal color Doppler ultrasound showed a hypervascularity in the uterus around the surgical lesion, suggesting a uterine AVM and its confirmed by angiography. The patient underwent a series of uterine artery embolization interventions, which proved to be a successful therapeutic approach. As a result of this treatment modality, not only was the patient's condition effectively resolved, but her fertility was also preserved.Conclusion: Acquired uterine arteriovenous malformation (AVM) is an uncommon sequela of cesarean section, warranting consideration in instances of persistent uterine bleeding in the puerperium. Embolization represents a viable and well-established treatment modality for AVM, providing a safe and efficacious intervention that serves as an alternative, less invasive modality for patients desiring fertility preservation.